Investigating the structural integrity of glass fiber reinforced polymer (GFRP) composite-striated reinforced concrete beams - Subramaniam, Navaneethan Kumaravalasu; Subbaiyan, Anandakumar; Velusamy, Sampathkumar; Shanmugamoorthy, Manoj (Matéria, 2024)
ABSTRACT This experimental study investigates the structural performance of reinforced concrete (RC) beams retrofitted with Glass Fiber-Reinforced Polymer (GFRP) composites. Retrofitting existing concrete structures has gained attention as an environmentally and economically viable method to enhance load-bearing capacity and extend lifespan. The study involves comprehensive experiments on RC beams with GFRP composites to improve the structural behavior of deteriorated or under-designed beams. RC beams representing common structural configurations, such as those with insufficient flexural capacity or corrosion, were fabricated. GFRP retrofitting involved applying sheets or strips to the tension and shear faces to enhance flexural strength and ductility. Parameters included the number of GFRP layers, their orientation, and bonding methods. Performance variables like load-carrying capability, deflection, cracking patterns, and failure modes were meticulously monitored. The research also explored the impact of GFRP retrofitting on environmental resistance and long-term endurance. Results are expected to provide insights into the effectiveness of GFRP composites for RC beam retrofitting, offering practical guidelines for engineers and researchers in rehabilitating and strengthening concrete structures, and advancing sustainable solutions for aging infrastructure.